Desenvolvimento de Podisus nigrispinus (Dallas, 1851) (Hetoroptera: Pentatomidae) em diferentes temperaturas e uso de soluções químicas para permeabilização de ovos - Santos, Ítala Tainy Barreto Francisco dos (2017)
Podisus nigrispinus Dallas (Heteroptera: Pentatomidae) is a stinkbug used in the biological control of several pests, and has therefore been massively reared in laboratories. Thus, with the objective of optimizing the mass rearing of P. nigrispinus by manipulating the temperature, two experiments were carried out: the first, aimed at investigating the effects of different temperatures on the development and on other biological characteristics of the predatory stinkbug; and the second, aimed at evaluating the processes of dechorionation and permeabilization in the viability of P. nigrispinus eggs with different embryonic ages. In the first experiment, four temperatures were used (17, 21, 25, and 29 °C ± 0.2), and the following parameters were evaluated: duration of the egg and nymphs stages; survival; adults longevity; number of eggs per female; pre-oviposition, oviposition and post-oviposition periods; adult weight and size. As result, an inversely proportional relationship was observed between the parameters duration of the egg and nymphs stages and survival at the temperatures studied. Longer adult longevity, pre-oviposition, oviposition and post-oviposition periods were obtained at a temperature of 17 °C. Conversely, the number of eggs, weight and size were adversely affected. Therefore, temperatures of 21 and 25 °C are the most suitable for the development of the predator; however, the extreme temperatures (17 and 29 °C) allowed delaying or accelerating the life cycle of the insect. In the second experiment, embryos of 24, 48, 72 and 96 hours of age were subjected to chemical solutions for dechorionation and permeabilization. Consequently, embryos with 96 hours of age presented greater viabilities, when compared with those with 24, 48 and 72 hours of age. Observations under a light microscope revealed differences in the chorion thickness after treatments with chemical solutions. Thus, the solutions for dechorionation and permeabilization of P. nigrispinus eggs together with embryonic age affect the viability of embryos to be cryopreserved.